Stabilization of Silicone Dioxide Nanoparticle Foam in Tertiary Petroleum Production - Mohd Zulkifli bin Mohamad Noor; Wong Yi Teng; Sonny Irawan (Indonesian Journal of Chemistry, 2019)
Nanoparticles have emerged with substantially to the end user and industrial applications. The applications initiated to enhance oil recovery (EOR) and also as alternative solution in increasing the rheological properties of fluids at difference condition. The study aims to evaluate the effects of various surfactant and nanoparticle concentration as well as hydrocarbons on foam stability. Series of static state experiments were conducted to investigate the foam development stability of five different concentrations for surfactant from 0.05 to 0.25 wt.% and nanoparticle from 0 to 1.00 wt.% in the presence of white mineral oil in synthetic brine suspension. By discussing to the Ross-Miles method - half-life capacities (t½), the foam stability of the aqueous foam was expected. Results suggested that the foam stability is increase with the present of nanoparticle. The 0.5 wt.% SiO2 nanoparticles enhanced foam formed the most lasting in the absence of white mineral oil as its t½ in presence of oil is 0.6 times smaller than in the absence of oil. It is concluded that the presence of nanoparticles for surfactant foam stability can be enhanced. The used of nanoparticles can be further study with different type of nanoparticles, only with small amount of nanoparticles used can further stabilize the foam.